Integral of e^(-x)*x^3 dx
The solution
Detail solution
-
Use integration by parts:
∫udv=uv−∫vdu
Let u(x)=x3 and let dv(x)=e−x.
Then du(x)=3x2.
To find v(x):
-
There are multiple ways to do this integral.
Method #1
-
Let u=−x.
Then let du=−dx and substitute −du:
∫eudu
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−eu)du=−∫eudu
-
The integral of the exponential function is itself.
∫eudu=eu
So, the result is: −eu
Now substitute u back in:
Method #2
-
Let u=e−x.
Then let du=−e−xdx and substitute −du:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−1)du=−∫1du
-
The integral of a constant is the constant times the variable of integration:
∫1du=u
So, the result is: −u
Now substitute u back in:
Now evaluate the sub-integral.
-
Use integration by parts:
∫udv=uv−∫vdu
Let u(x)=−3x2 and let dv(x)=e−x.
Then du(x)=−6x.
To find v(x):
-
Let u=−x.
Then let du=−dx and substitute −du:
∫eudu
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−eu)du=−∫eudu
-
The integral of the exponential function is itself.
∫eudu=eu
So, the result is: −eu
Now substitute u back in:
Now evaluate the sub-integral.
-
Use integration by parts:
∫udv=uv−∫vdu
Let u(x)=6x and let dv(x)=e−x.
Then du(x)=6.
To find v(x):
-
Let u=−x.
Then let du=−dx and substitute −du:
∫eudu
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−eu)du=−∫eudu
-
The integral of the exponential function is itself.
∫eudu=eu
So, the result is: −eu
Now substitute u back in:
Now evaluate the sub-integral.
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−6e−x)dx=−6∫e−xdx
-
Let u=−x.
Then let du=−dx and substitute −du:
∫eudu
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−eu)du=−∫eudu
-
The integral of the exponential function is itself.
∫eudu=eu
So, the result is: −eu
Now substitute u back in:
So, the result is: 6e−x
-
Now simplify:
(−x3−3x2−6x−6)e−x
-
Add the constant of integration:
(−x3−3x2−6x−6)e−x+constant
The answer is:
(−x3−3x2−6x−6)e−x+constant
The answer (Indefinite)
[src]
/
|
| -x 3 -x 3 -x -x 2 -x
| e *x dx = C - 6*e - x *e - 6*x*e - 3*x *e
|
/
∫x3e−xdx=C−x3e−x−3x2e−x−6xe−x−6e−x
The graph
Use the examples entering the upper and lower limits of integration.